Enhancing Organizational Commitment: The Role of Job Satisfaction in the Relationship Between Compensation and Work Environment in High Schools - Ningsih, Ni Luh Anik Puspa; Wandari, Putu Arika; Ngurah Suyatna Yasa, Putu; Indiani, Ni Luh Putu; Sara, I Made; Amertha, I Made Suniastha (Oeconomica Jadertina, 2026)
In the school context, organizational commitment greatly affects the quality of teaching, interaction between teachers and students, and overall academic progress. The purpose of this study is to examine and analyze the effect of compensation and work environment on organizational commitment mediated by job satisfaction in high schools in north Indonesia. This research uses quantitative methods and is analyzed using structural equation modelling partial least squares (SEM-PLS). The number of respondents in this study was 58 respondents because the target of this study was non-permanent teachers. The results of this study indicate that compensation has a positive insignificant effect on organizational commitment, compensation has a positive significant effect on job satisfaction, (3) work environment has a negative insignificant effect on organizational commitment,  work environment has a positive insignificant effect on job satisfaction, job satisfaction has a significant positive effect on organizational commitment, job satisfaction mediates the relationship between compensation and organizational commitment, job satisfaction does not mediate the relationship between work environment and organizational commitment. Furthermore, future research can also conduct a comparative study with permanent teachers to ascertain the established or otherwise relationship of the research constructs.
Keywords: Compensation, Work Environment, Job Satisfaction, Employee Commitment